COMPREHENSIVE DEVELOPMENT OF ASSOCIATED MINERALS AND COAL COMPONENTS OF THE LYUBELYA DEPOSIT OF THE LVIV-VOLYN BASIN - Buchynska, І.; Matrofaylo, М.; Poberezhskyy, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The potential of coal deposits is determined not only by the establishment of coal bearing capacity, but also by a number of criteria determined by the complex extraction of associated minerals and coal components. One of the main reserves of replenishment of the mining mine fund of the Lviv-Volyn coal basin (LVB) is the South-Western coal-bearing area. The Lyubelya coal deposit is located in the south-western part of the Lviv-Volyn basin within the Kariv syncline.The Lyubelya deposit is the most submerged part of the LVB with the most complete stratigraphic section. The coal-bearing stratum is gas-bearing and germanium-bearing. Integrated use of the raw material base of LVB with the use of certain technologies of preliminary gas extraction will help to increase the profitability of the coal mining complex and prevent accidents. The deposit has significant reserves of high-quality coal that can be used for coking, which will be a significant contribution to the development of the Ukraine's energy base. Coal of grades Zh, KZh and K is widespread at the Lyubelya deposit. Coking coal makes up almost half of the field's reserves. The total explored coal reserves are 522884 thousand tons. Significant degassing of the coal seam in combination with high technological qualities of coal is the reason for the increased interest in the Lyubelya deposit. In its southern part, gas is almost absent in the fields of the Lyubelya mines No. 1 and 2, within the depths of the main working layers. But coal seams v6 , п06, п7 , п71 , п7в, п8 , п9 lie in the methane gas zone in the fields of Lyubelya mines No. 1–4 and are characterized by high natural gas content – from 9.60 to 30.70 m 3/t s.b. Methane gas zone is immersed in the direction of the bottom of the Kariv syncline. When designing coal mining in the deep horizons of the Lyubelya field, it is necessary to take into account their gas potential and the possibility of degassing of coal seams. Сoal gas can be considered as a stand-alone mineral that can be extracted in sufficient quantities and economically feasible. Coal from the Lyubelya deposit may also be suitable as a raw material for the extraction of germanium. Thus, the estimated reserves of germanium in terms of actual content in the coal of the Lyubelya No. 3 section in category C2 amounted to 248.41 tons.The Lyubelya deposit of LVB has significant reserves of high-quality coal that can be used for coking, which will be a significant contribution to the development of the Ukraine's energy base. When designing cost-effective technological schemes of coal mining, it is necessary to take into account the whole set of indicators for the development of related minerals and coal components.
Keywords: coal reserves; gas-bearing capacity; Germanium-bearing capacit; complex us; Lyubelya deposit; Lviv-Volyn basin